An Analysis of Urban Poverty and Unemployment - Faturohim, Agus; Akbar, Alexander; Hidayat, Bachtari Alam; Saksono, Herie (Research and Development Agency Ministry of Home Affairs, 2023)
The success of development depicts economic growth. Nevertheless, it is pertinent to emphasize that a significant increase in economic growth may not eradicate poverty, unemployment, and health issues. The prevalence of poverty in Palembang City in 2021 was considerably elevated, amounting to 11.34 percent, while the unemployment rate has exhibited an upward trend, reaching 10.11 percent. Additionally, there was a decline in employment within the labor market, accompanied by a corresponding rise in the number of individuals actively seeking job opportunities. This study aims to examine the various elements contributing to poverty and unemployment and formulate an integrated and sustainable model for poverty reduction and lowering unemployment in urban areas. The data collection technique uses a concurrent mixed method through questionnaires distributed to the public by purposive random sampling of 215 informants and Focus Group Discussions with relevant stakeholders in Palembang City in November 2022. The results of the study found that four factors contribute to poverty in Palembang City: education level, economic growth, health, and labor force participation rate. The level of education is the most dominant factor that plays a role in the occurrence of poverty and unemployment in Palembang City. The strategy formulated is the provision of educational scholarship programs for poor families at the primary and secondary education levels through the utilization of operational costs. It can be concluded that education has a big role in reducing poverty and unemployment, so it is important to invest in education. Investment in education, including improved access and quality of education, can help address issues of poverty and unemployment by giving individuals better opportunities for decent work.